2018
DOI: 10.1121/1.5037585
|View full text |Cite
|
Sign up to set email alerts
|

On the use of a stress–impedance model to describe sound propagation in a lined duct with grazing flow

Abstract: With flow, the acoustic effect of a locally reacting lined wall cannot be described by a single quantity independent of the incident wave, such as a wall impedance. At least two quantities, intrinsic to the liner and to the flow, are required to describe the effect of the lined wall regardless of the incident wave. In addition to the impedance, the unsteady tangential force exerted by the wall on the flow has to be taken into account. This force is due either to viscous effects or to the unsteady transfer of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…It is also shown that a correlation exists between the remaining impedance mismatch and the uncertainties obtained via the Bayesian inference eduction, showing that the two quantities might relate to the same phenomenon (larger uncertainties when the liner is not absorbent). Another possibility is the presence of unmodeled physics of the impedance boundary condition, which is still an ongoing research topic [42,43]. However, the present work shows that the refinement of physics modeling will require accounting for the experimental uncertainties in impedance eduction.…”
Section: Discussionmentioning
confidence: 89%
“…It is also shown that a correlation exists between the remaining impedance mismatch and the uncertainties obtained via the Bayesian inference eduction, showing that the two quantities might relate to the same phenomenon (larger uncertainties when the liner is not absorbent). Another possibility is the presence of unmodeled physics of the impedance boundary condition, which is still an ongoing research topic [42,43]. However, the present work shows that the refinement of physics modeling will require accounting for the experimental uncertainties in impedance eduction.…”
Section: Discussionmentioning
confidence: 89%
“…At the entrance of each hole a resistive sheet with R = 0.0175 has been added, which accounts for the thermo-viscous effects. This value has been empirically chosen so that, in § 4, both unstable and stable global modes can be obtained by slightly adjusting R. Such a resistance can also mitigate the convergence problem of the calculations, which is caused by the discontinuity of df /dy at y = 1 (Dai & Aurégan 2016, 2018. It has been shown that sound can be amplified by this non-local liner at certain frequencies (Dai & Aurégan 2019).…”
Section: Large-scale Hydrodynamic Instability Along a Perforated Platementioning
confidence: 99%
“…However, it should be noted that such an impedance model can lead to inaccuracy in describing wave propagation in a flow duct, especially when the flow velocity is high (Dai & Aurégan 2016;Aurégan 2018). For this reason, only a qualitative comparison can be made between the discrete and homogenized models, and a quantitative agreement requires a more precise homogenization of a perforated plate with flow.…”
Section: Global Mode Analysismentioning
confidence: 99%
See 2 more Smart Citations